Gone but Not Forgotten: The Transformation of the Idea of Islamic State through Traditional Religious Authorities - Pamungkas, Cahyo (Masyarakat: Jurnal Sosiologi, 2018)
Much of scholars state that a number of new religious authorities support religious conservatism. This article shows that the old religious authorities also became the driving force of Islamic conservatism and identity politics in East Priangan, West Java, especially those historically tied to the Darul Islam movement. This article aims to narrate the transformation of the idea of Islamic State (Darul Islam) into the Sharia-compliant Republic of Indonesia, which is taking place in the East Priangan region. In 2016, supporters of this idea were among the most enthusiastic participants of the 212 rallies in Jakarta. This article uses qualitative research by using the data collection methods of literature study, observation, and interviews with heads of pesantren in Tasikmalaya and Ciamis. It shows that religious movements in East Priangan play a significant role in supporting Islamic populism at the national level. The argument is that some traditional pesantren or religious organizations support religious conservatism that continues in the era of identity politics.